2019
DOI: 10.1186/s12944-019-1143-z
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 polyunsaturated fatty acids status and cognitive function in young women

Abstract: BackgroundResearch indicates that low omega-3 polyunsaturated fatty acid (n-3 PUFA) may be associated with decreased cognitive function. This study examined the association between n-3 PUFA status and cognitive function in young Australian women.MethodsThis was a secondary outcome analysis of a cross-sectional study that recruited 300 healthy women (18–35 y) of normal weight (NW: BMI 18.5–24.9 kg/m2) or obese weight (OB: BMI ≥30.0 kg/m2). Participants completed a computer-based cognition testing battery (Integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…Throughout life, from age four years to the second half of the eighties, at all ages investigated, complex cognitive functions, like problem solving behavior, executive function, or aspects of memory correlated with the Omega-3 Index [ 102 , 103 , 104 , 105 , 106 , 107 ]. Similar results were found, when blood levels of EPA and DHA were assessed differently, and for DHA in a recent meta-analysis [ 108 , 109 , 110 , 111 ]. A low Omega-3 Index predisposes to a more rapid cognitive decline and an earlier onset of dementia compared to a higher Omega-3 Index [ 105 , 112 , 113 ].…”
Section: Brain Health In Adulthood–cognition and Dementiasupporting
confidence: 85%
“…Throughout life, from age four years to the second half of the eighties, at all ages investigated, complex cognitive functions, like problem solving behavior, executive function, or aspects of memory correlated with the Omega-3 Index [ 102 , 103 , 104 , 105 , 106 , 107 ]. Similar results were found, when blood levels of EPA and DHA were assessed differently, and for DHA in a recent meta-analysis [ 108 , 109 , 110 , 111 ]. A low Omega-3 Index predisposes to a more rapid cognitive decline and an earlier onset of dementia compared to a higher Omega-3 Index [ 105 , 112 , 113 ].…”
Section: Brain Health In Adulthood–cognition and Dementiasupporting
confidence: 85%
“…However, contrary to these results, Cook et al [102] reported that cognitively healthy young women with lower omega-3s had lower attention scores. Therefore, discrepancies between these studies might be due to gender differences in absorption and/or response to omega-3 fatty acid supplementation.…”
Section: Pufas Supplementsmentioning
confidence: 78%
“…Regardless of the mechanism through which omega-3 supplement use stabilizes CBF, the consequent increased delivery of oxygen and nutrients to the brain could explain findings from other studies that show omega-3 fatty acids augment cognitive function and prevent cognitive decline [39][40][41][42]. For example, the connection between atherosclerosis and dementia has been well-established [43], and a meta-analysis of randomized controlled trials showed that omega-3 fatty acids significantly slowed the progression of atherosclerosis [44], suggesting that omega-3 fatty acids could potentially prevent cognitive decline through improvements in vascular health.…”
Section: Discussionmentioning
confidence: 99%